Appropriate Nonlocal Hydrodynamic Models for the Characterization of Deep‐Nanometer Scale Plasmonic Scatterers. Issue 1 (18th November 2019) - Kupresak, Mario; Zheng, Xuezhi; Vandenbosch, Guy A. E.; Moshchalkov, Victor V.
Abstract: The interaction between light and plasmonic systems with deep‐nanometer characteristics, which is essentially governed by quantum mechanical effects, has been extensively studied by the nonlocal hydrodynamic approach. Several hydrodynamic models, supplemented by additional boundary conditions, have been introduced in order to describe the collective motion of the free electron gas in metals. Four hydrodynamic models, namely the hard wall hydrodynamic model (HW‐HDM), the curl‐free hydrodynamic model, the shear forces hydrodynamic model, and the quantum hydrodynamic model (Q‐HDM), are thoroughly investigated. The investigation studies the mode structure (the natural modes or, in quantum optics, the quasi‐normal modes) of the spherical core–shell topology, which is complemented by the plane wave response from the system. The results of the above hydrodynamic models are also compared with those of the specular reflection method. It is demonstrated that the choice of a particular hydrodynamic model strongly affects the natural frequencies and modes in the mode structure of the topology and thus drastically modifies the simulated fields in the near and far regions. Contrary to HW‐HDM and Q‐HDM, the other two hydrodynamic models fail to predict the particles' response accurately, showing artifactual mode hybridization. Abstract : Four nonlocal hydrodynamic approaches with additional boundary conditions, which tackle the non‐classical effects at deep‐nanometer scale, are fully investigated. The investigation is performed for the mode structure (natural modes) of the spherical core–shell topology, supplemented by the plane wave response of the system. It is shown that not all hydrodynamic models perform accurately.